2013
DOI: 10.2147/dmso.s33943
|View full text |Cite
|
Sign up to set email alerts
|

Management of limited joint mobility in diabetic patients

Abstract: Several rheumatologic manifestations are more pronounced in subjects with diabetes, ie, frozen shoulder, rotator cuff tears, Dupuytren’s contracture, trigger finger, cheiroarthropathy in the upper limb, and Achilles tendinopathy and plantar fasciitis in the lower limb. These conditions can limit the range of motion of the affected joint, thereby impairing function and ability to perform activities of daily living. This review provides a short description of diabetes-related joint diseases, the specific pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
101
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(102 citation statements)
references
References 107 publications
0
101
0
1
Order By: Relevance
“…Also, other factors like pentosidine concentration or altered gait might play a role. Abate et al 17 concluded in their review that many complex pathogenetic mechanisms are involved in rheumatological manifestations of diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, other factors like pentosidine concentration or altered gait might play a role. Abate et al 17 concluded in their review that many complex pathogenetic mechanisms are involved in rheumatological manifestations of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycaemia itself may also increase expression of matrix metalloproteinase-9 and metalloproteinase-13 in tendon cells and impair collagen synthesis 16. Nevertheless, the pathomechanics behind tendon degeneration in either type 1 or type 2 diabetes is most likely multifactorial and still largely unknown 12 17…”
Section: Introductionmentioning
confidence: 99%
“…Satisfaction rate was high and disability returned to normal after surgery. The patients with diabetes, a known metabolic disturbance quite often leading to therapy resisting tendinosis, all recovered as well after surgery as the idiopathic forms [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Factors such as compliance (11) and exercise responsiveness (12,13) complicate the development and implementation of clear physical activity recommendations and/or guidelines for people with IGT or overt type 2 diabetes. Furthermore, older individuals may be restricted or limited in their exercise modality because of prior illness, reduced mobility, or other complications (14). In addition, controlled, supervised exercise trials do not necessarily reflect the actual adherence to an exercise prescription offered by many primary care professionals.…”
mentioning
confidence: 99%